Produção de mudas de eucalipto em vermicomposto com lodo de esgoto, resíduos vegetais e terra diatomácea - Fabiola Mendes Braga (2016)
The search for residue recovery has been the best way to contribute to the environmental sustainability. By combining the waste formed in the treatment of sewage and the residue formed in the biofuel production is possible to form a substrate rich in minerals and organic matter by vermicomposting. The chemical benefits of sewage sludge (SS) and the physical benefits of diatomaceous earth (DE) can have synergisticaction and become great soil conditioners for various crops, including eucalyptus. In this way, the objective was to produce a vermicompost from a pre-compost (PC) of sewage sludge and prunings of gardening residue with different proportions of DE coming from the process of manufacturing biofuel oil. The substrates were packed in 100 Lcontainers together with Eisenia foetida earthworms with the following proportions of PC and DE: T1:100%PC and 0%DE, T2: 92,47%PC and 7,53%DE, T3: 84,94%PC and 15,06%DE, T4: 77,41%PC and 22,59%DE and T5: 69,88%PC and 30,12%DE. The experiment in the randomized block design consisted of 5 treatments and 5 replicates. After 4 months, samples were taken from each treatment and nutrients and heavymetals analyzed. A second experiment was carried out with the above-mentioned substrates, and a control with a commercial substrate, in which Eucalipto urophylla seedlings were grown. A second experiment was carried out in a randomized complete block design with 6 treatments and 5 replicates. After 90 days, a sample of each experimental unit was collected and taken to the laboratory for analysis of nutrients andheavy metals and plant physical analyzes, such as stem diameter (DC), plant height (H) ratio DC/M, Dickson quality index (DCI), fresh and dry mass of the plant. The results were analyzed by applying the Dunnett test to the control and adjusted to the regression equations for the other treatments. The vermicompost of sewage sludge, plant residuesand diatomaceous earth in the proportion of 30,12% v/v met all criteria established for agricultural use and registration and commercialization of the product as organic compost, as established in the Resolution CONAMA 375 and in the Normative Instructions of the Ministry of Agriculture (IN SDA 27/2006). In general, it was found that the substrates formed from vermicompost and DE provided suitable chemical and10 physical conditions and close to the commercial substrate for E. urophylla seedling growth.